Low-refractive adhesive composition, adhesive tape product and preparation method thereof

By using components such as long-chain acrylate monomer, fluoro-containing acrylate monomer and propionate functional monomer in the adhesive, combined with high-temperature polymerization technology, a low refractive adhesive is prepared, which solves the problem of insufficient optical performance and adhesive strength in VR equipment, and a low refractive index and high transmittance adhesive is achieved.

CN116333651BActive Publication Date: 2025-03-04TAICANG SIDIKE NEW MATERIALS SCI & TECH CO LTD +2
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310249697.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-15
Publication Date
2025-03-04
Estimated Expiration
2043-03-15

AI Technical Summary

Technical Problem

Existing adhesives cannot meet the needs of low refractive index and high transmittance in the optical structure of virtual reality (VR) devices, affecting their optical properties and bonding strength.

Method used

A low refractive adhesive composition is adopted, including long-chain acrylate monomer, fluorine-containing acrylate monomer, propionate functional monomer, solvent and initiator, and is prepared by high-temperature polymerization technology to achieve a balance of low refractive index and high bonding strength.

Benefits of technology

It realizes optically transparent low-refractive adhesive, with a refractive index of less than 1.4, an adhesive strength of more than 10N, and has high transmittance and low haze, which is suitable for bonding applications of VR and AR equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004127393720000081
    Figure BDA0004127393720000081
  • Figure BDA0004127393720000091
    Figure BDA0004127393720000091
Patent Text Reader

Abstract

The present invention discloses a low-refractive adhesive composition, a tape product and a preparation method thereof, wherein the low-refractive adhesive composition comprises the following components by weight: 40-85 parts of a long-chain acrylate monomer (containing 7 or more C atoms on the main chain), 5-15 parts of a hydroxyl- or carboxyl-containing propionate functional monomer, 10-50 parts of a fluorine-containing acrylate monomer, 50-200 parts of a solvent and 0.2-2 parts of an initiator. The present invention prepares an optically transparent low-refractive adhesive composition, the refractive index of which can reach less than 1.4, the bonding strength of which can reach more than 10N, and the tape product also has high transmittance and low haze; the tape product prepared based on the low-refractive adhesive composition has excellent optical properties, step filling properties, bonding properties and low refractive index, can be used for bonding of equipment materials such as VR and AR, and has good application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of adhesive materials, and in particular to a low-refractive adhesive composition, an adhesive tape product and a preparation method thereof. Background Art

[0002] Adhesives can be divided into epoxy resin adhesives, polyurethane adhesives, silicone adhesives, acrylate adhesives, etc. according to their chemical composition. They are widely used because of their high strength, good flexibility, light weight, low pollution, and non-destructive properties. Therefore, in recent years, the market share of adhesives in the fields of automobiles, electronics, ships, medical treatment, aerospace, etc. has continued to rise. At present, virtual reality technology is becoming more and more mature and has applications in medicine, games, military aerospace, interior design, real estate development, industrial simulation, cultural relics and other fields. VR equipment is an important tool for building virtual reality, and optical structure is the core technology of VR. With the continuous iteration of optical structure, VR equipment has put forward new requirements in terms of material refractive index. Summary of the invention

[0003] The technical problem to be solved by the present invention is to provide a method for addressing the deficiencies in the above-mentioned prior art.

[0004] In order to solve the above technical problems, the technical solution adopted by the present invention is: a low-refractive adhesive composition, comprising the following components in parts by weight:

[0005] 40-85 parts of long-chain acrylate monomer, 5-15 parts of hydroxyl- or carboxyl-containing propionate functional monomer, 10-50 parts of fluorine-containing acrylate monomer, 50-200 parts of solvent and 0.2-2 parts of initiator;

[0006] Wherein, the long-chain acrylate monomer is an acrylate monomer containing 7 or more C atoms in the main chain;

[0007] The preparation method of the low-refractive adhesive composition comprises the following steps:

[0008] 1) Add 40-85 parts of long-chain acrylate monomer, 5-15 parts of propionate functional monomer, 10-50 parts of fluorine-containing acrylate monomer, and 50-200 parts of solvent into a reaction kettle, pass nitrogen for 20-40 minutes under stirring conditions, maintain the temperature above 75° C., add 0.1-1 parts of initiator and react for 2-10 hours;

[0009] 2) raising the temperature to above 78° C., adding 0.1 to 1 part of an initiator, and reacting for 2 to 10 hours; and cooling to obtain the low-refractive adhesive composition.

[0010] Preferably, the long-chain acrylate monomer is selected from one or more of butyl acrylate, isooctyl acrylate, n-pentyl acrylate, n-hexyl acrylate, lauryl acrylate, n-octyl acrylate, isostearyl acrylate, isodecyl acrylate, methoxy polyethylene glycol acrylate, and tridecyl methacrylate.

[0011] Preferably, the propionate functional monomer is selected from one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, and hydroxypropyl methacrylate.

[0012] Preferably, the fluorine-containing acrylic monomer is selected from one or more of trifluoroethyl acrylate, trifluoroethyl methacrylate, pentafluoroethyl acrylate, pentafluoroethyl methacrylate, octafluoropentyl methacrylate, heptafluorobutyl acrylate, tridecafluorooctyl acrylate, pentafluorooctyl acrylate, heptadecafluorodecyl methacrylate and heptadecafluorononyl methacrylate.

[0013] Preferably, the initiator is one or more of an azo initiator and a peroxide initiator.

[0014] Preferably, the initiator is azobisisobutyronitrile, benzoyl peroxide or a mixture of both.

[0015] The present invention also provides an adhesive tape product, which is prepared by the following steps:

[0016] The low-refractive adhesive composition as described above is mixed with a curing agent, and after being evenly mixed, the mixture is coated on a release film, and after drying, another layer of release film is attached to the surface, and the mixture is aged to obtain an adhesive tape product.

[0017] Preferably, the adhesive tape product is prepared by the following steps:

[0018] 98-99.9 parts by weight of the low-refractive adhesive composition according to any one of claims 1 to 6 are mixed with 0.1-2 parts by weight of a curing agent, mixed evenly and coated on a release film, baked at 100-120° C. for 1-4 minutes, and then a layer of release film is attached to the surface, and aged at 50-70° C. for 72 hours to obtain a tape product.

[0019] Preferably, the curing agent is selected from one or more of an isocyanate curing agent, an epoxy resin curing agent, an aziridine curing agent, and a metal chelate compound curing agent;

[0020] When the propionate functional monomer contains a hydroxyl group, an isocyanate curing agent is selected; when the propionate functional monomer contains a carboxyl group, one or more of an isocyanate curing agent, an epoxy resin curing agent, an aziridine curing agent, and a metal chelate compound curing agent is selected.

[0021] Preferably, the epoxy resin curing agent is selected from: one or more of P-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline, triglycidyl-m-aminophenol, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraepoxypropyl-4,4'-diaminodiphenylmethane;

[0022] The aziridine curing agent is selected from: one or more of trimethylolpropane-tris[3-(2-methylaziridinyl) propionate], pentaerythritol tris[(3-(1-aziridinyl) propionate], and trimethylolpropane tris(3-aziridinyl propionate);

[0023] The metal chelate compound curing agent is selected from one or more of: aluminum triacetylacetonate, iron triacetylacetonate, ruthenium triacetylacetonate, zinc diacetylacetonate, titanium triacetylacetonate, zirconium tetraacetylacetonate, tri(2,4-hexanedione)aluminum.

[0024] The beneficial effects of the present invention are:

[0025] The present invention prepares an optically transparent low-refractive adhesive composition, whose refractive index can reach below 1.4, and whose bonding strength can reach above 10N, and which also has high transmittance and low haze; the adhesive tape product prepared based on the low-refractive adhesive composition has excellent optical properties, step-filling properties, bonding properties and low refractive index, can be used for bonding materials of equipment such as VR and AR, and has good application prospects. DETAILED DESCRIPTION

[0026] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0027] It should be understood that terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0028] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0029] The present invention provides a low-refractive adhesive composition, comprising the following components in parts by weight:

[0030] 40-85 parts of long-chain acrylate monomer, 5-15 parts of hydroxyl- or carboxyl-containing propionate functional monomer, 10-50 parts of fluorine-containing acrylate monomer, 50-200 parts of solvent and 0.2-2 parts of initiator;

[0031] Among them, the long-chain acrylate monomer is an acrylate monomer containing 7 or more C atoms in the main chain, which has excellent wettability; the hydroxyl- or carboxyl-containing propionate functional monomer can improve the cohesive strength and adhesion through cross-linking; the fluorine-containing acrylate monomer has the characteristic of low refraction.

[0032] The weight average molecular weight of the above acrylic acid monomer copolymer is at least 100,0000, more preferably at least 120,0000.

[0033] The preparation method of the low-refractive adhesive composition comprises the following steps:

[0034] 1) Add 40-85 parts of long-chain acrylate monomer, 5-15 parts of propionate functional monomer, 10-50 parts of fluorine-containing acrylate monomer, and 50-200 parts of solvent into a reaction kettle, pass nitrogen for 20-40 minutes under stirring conditions, maintain the temperature above 75° C., add 0.1-1 parts of initiator and react for 2-10 hours;

[0035] 2) Raising the temperature to above 78°C, adding 0.1-1 part of initiator, reacting for 2-10 hours, and cooling to obtain the low-refractive adhesive composition. In this process, high-temperature polymerization can solve the problem that the conventional process fluorine-containing monomer cannot be well copolymerized with ordinary acrylic monomer.

[0036] In a preferred embodiment, the long-chain acrylate monomer is selected from one or more of butyl acrylate, isooctyl acrylate, n-pentyl acrylate, n-hexyl acrylate, lauryl acrylate, n-octyl acrylate, isostearyl acrylate, isodecyl acrylate, methoxy polyethylene glycol acrylate, and tridecyl methacrylate.

[0037] In a preferred embodiment, the propionate functional monomer is selected from one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, and hydroxypropyl methacrylate.

[0038] In a preferred embodiment, the fluorine-containing acrylic monomer is selected from: one or more of trifluoroethyl acrylate, trifluoroethyl methacrylate, pentafluoroethyl acrylate, pentafluoroethyl methacrylate, octafluoropentyl methacrylate, heptafluorobutyl acrylate, tridecafluorooctyl acrylate, pentafluorooctyl acrylate, heptadecafluorodecyl methacrylate, and heptadecafluorononyl methacrylate.

[0039] In a preferred embodiment, the initiator is one or more of an azo initiator and a peroxide initiator. Further preferably, the initiator is one or a mixture of azobisisobutyronitrile and benzoyl peroxide.

[0040] In a preferred embodiment, the solvent is an organic solvent such as ethyl acetate, toluene, or butanone.

[0041] The present invention also provides an adhesive tape product, which is prepared by the following steps:

[0042] 98-99.9 parts by weight of the above low-refractive adhesive composition is mixed with 0.1-2 parts by weight of a curing agent, mixed evenly and coated on a release film, baked at 100-120° C. for 1-4 minutes, and then a layer of release film is attached to the surface, and aged at 50-70° C. for 72 hours to obtain a tape product.

[0043] Wherein, the curing agent is selected from one or more of an isocyanate curing agent, an epoxy resin curing agent, an aziridine curing agent, and a metal chelate compound curing agent;

[0044] When the propionate functional monomer contains a hydroxyl group, an isocyanate curing agent is selected; when the propionate functional monomer contains a carboxyl group, one or more of an isocyanate curing agent, an epoxy resin curing agent, an aziridine curing agent, and a metal chelate compound curing agent is selected.

[0045] In a preferred embodiment, the epoxy resin curing agent is selected from: one or more of P-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline, triglycidyl-m-aminophenol, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraepoxypropyl-4,4'-diaminodiphenylmethane;

[0046] The aziridine curing agent is selected from: one or more of trimethylolpropane-tris[3-(2-methylaziridinyl) propionate], pentaerythritol tris[(3-(1-aziridinyl) propionate], and trimethylolpropane tris(3-aziridinyl propionate);

[0047] The metal chelate compound curing agent is selected from one or more of: aluminum triacetylacetonate, iron triacetylacetonate, ruthenium triacetylacetonate, zinc diacetylacetonate, titanium triacetylacetonate, zirconium tetraacetylacetonate, tri(2,4-hexanedione)aluminum.

[0048] In the present invention, by adjusting the amount of curing agent, the gel fraction of the adhesive film (tape product) is controlled to be above 50% and below 85%, more preferably above 55% and below 75%, so that the adhesive film has excellent step filling property while maintaining high cohesive strength and adhesive performance. The storage modulus G of the prepared adhesive film at 25°C and 1 Hz is at least about 1×104 Pa and at most about 5×10 5 Pa, storage modulus is affected by factors such as the type of monomer of the adhesive, the size of the molecular weight, the proportion of the adhesive, etc. The above factors can be adjusted to achieve a suitable modulus. The film within this modulus range has an excellent balance between cohesive strength and bonding strength.

[0049] The adhesive tape product of the present invention has excellent optical properties, step-difference filling properties, bonding properties and low refractive index, and can be used for bonding VR and AR equipment materials.

[0050] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.

[0051] Example 1

[0052] 60 parts of isooctyl acrylate, 5 parts of acrylic acid, 35 parts of tridecafluorooctyl acrylate and 100 parts of ethyl acetate were added to the reactor in parts by weight. Nitrogen was passed through the reactor under stirring to remove air, 0.3 parts of benzoyl peroxide was added, and the temperature was maintained at 75° C. for 4 hours; the temperature was raised to 78° C., 0.3 parts of azobisisobutyronitrile was added, and the temperature was maintained for 6 hours; and the low-refractive adhesive composition was obtained by cooling.

[0053] Example 2

[0054] 40 parts of isooctyl acrylate, 5 parts of acrylic acid, 55 parts of tridecafluorooctyl acrylate and 100 parts of ethyl acetate were added to the reactor in parts by weight. Nitrogen was passed through the reactor under stirring to remove air, 0.3 parts of benzoyl peroxide was added, and the temperature was maintained at 75° C. for 4 hours; the temperature was raised to 78° C., 0.3 parts of azobisisobutyronitrile was added, and the temperature was maintained for 6 hours; and the low-refractive adhesive composition was obtained by cooling.

[0055] Example 3

[0056] 50 parts of isooctyl acrylate, 10 parts of acrylic acid, 45 parts of tridecafluorooctyl acrylate and 100 parts of ethyl acetate were added to the reactor in parts by weight. Nitrogen was passed through the reactor under stirring to remove air, 0.3 parts of benzoyl peroxide was added, and the temperature was maintained at 75° C. for 4 hours; the temperature was raised to 78° C., 0.3 parts of azobisisobutyronitrile was added, and the temperature was maintained for 6 hours; and the low-refractive adhesive composition was obtained by cooling.

[0057] Example 4

[0058] 50 parts of isooctyl acrylate, 10 parts of hydroxyethyl acrylate, 45 parts of tridecafluorooctyl acrylate and 100 parts of ethyl acetate were added to the reactor in parts by weight. Nitrogen was passed through the reactor under stirring to remove air, 0.3 parts of benzoyl peroxide was added, and the temperature was maintained at 75° C. for 4 hours; the temperature was raised to 78° C., 0.3 parts of azobisisobutyronitrile was added, and the temperature was maintained for 6 hours; and the low-refractive adhesive composition was obtained by cooling.

[0059] Comparative Example 1

[0060] 60 parts of isooctyl acrylate, 5 parts of acrylic acid, 35 parts of butyl acrylate and 100 parts of ethyl acetate were added to the reactor in parts by weight. Nitrogen was passed through the reactor under stirring to remove air, 0.3 parts of benzoyl peroxide was added, and the temperature was maintained at 75° C. for 4 hours; the temperature was raised to 78° C., 0.3 parts of azobisisobutyronitrile was added, and the temperature was maintained for 6 hours; and the adhesive composition was obtained by cooling.

[0061] Comparative Example 2

[0062] 64 parts of isooctyl acrylate, 1 part of acrylic acid, 35 parts of tridecafluorooctyl acrylate and 100 parts of ethyl acetate were added to the reactor in parts by weight. Nitrogen was passed through the reactor under stirring to remove air, 0.3 parts of benzoyl peroxide was added, and the temperature was maintained at 75° C. for 4 hours; the temperature was raised to 78° C., 0.3 parts of azobisisobutyronitrile was added, and the temperature was maintained for 6 hours; and the adhesive composition was obtained by cooling.

[0063] Comparative Example 3

[0064] 40 parts of methyl acrylate, 5 parts of acrylic acid, 55 parts of tridecafluorooctyl acrylate and 100 parts of ethyl acetate were added to the reactor in parts by weight. Nitrogen was passed through the reactor under stirring to remove air, 0.3 parts of benzoyl peroxide was added, and the temperature was maintained at 75° C. for 4 hours; the temperature was raised to 78° C., 0.3 parts of azobisisobutyronitrile was added, and the temperature was maintained for 6 hours; and the adhesive composition was obtained by cooling.

[0065] The adhesive compositions prepared in Examples 1-4 and Comparative Examples 1-3 were used to prepare tape product samples according to the ratios in Table 1 below by the following method: the adhesive composition and the curing agent were mixed and stirred evenly, coated on a 100 μm release film (polyester film) using a scraper coater, and a coating with a thickness of 100 μm was prepared according to the solid content calculation, baked at 110° C. for 2 min, and then covered with a 50 μm release film (polyester film), aged at 55° C. for 72 hours, and then taken out to prepare a tape product sample.

[0066] Table 1

[0067] Adhesive composition L-75 curing agent Tetrad-C Epoxy Curing Agent Ratio 1 Example 1 0.2% - Ratio 2 Example 2 0.2% Ratio 3 Example 2 0.2% 0.1% Ratio 4 Example 3 - 0.5% Ratio 5 Example 3 - 5% Ratio 6 Example 4 0.2% - Ratio 7 Comparative Example 1 0.2% - Ratio 8 Comparative Example 2 0.2% - Ratio 9 Comparative Example 3 0.2% - Ratio 10 Comparative Example 3 0.2% 0.1%

[0068] The adhesive tape product samples obtained by the above 9 ratios were subjected to the following performance tests.

[0069] (1) Peel strength: Peel off one side of the polyester film (release film) of the film with a ratio of 1-9, and stick it on a 0.05MM transparent PET film. Cut it into samples with a width of 25.4mm and a length of 300mm. Peel off the other side of the polyester film (release film), and use a 2KG roller to roll it on a SUS 304 steel plate at a speed of 600MM / MIN. Let it stand for 20 minutes, and use a tensile tester to test its 180° peeling adhesion. The specific test method refers to the ASMTD3330 international standard.

[0070] (2) Refractive Index: The refractive index of the film was measured using an Abbe refractometer (manufactured by ATAGO Corporation, model “DR-M4”) at a measurement wavelength of 589 nm and a measurement temperature of 25°C.

[0071] (3) Storage modulus: A sample for measurement was obtained by laminating each pressure-sensitive adhesive film layer to a thickness of about 1.5 mm. The dynamic viscoelasticity was measured under the following conditions using ARES manufactured by TA Instruments. The storage modulus G' at 25°C was read from the measurement results.

[0072] (4) Transmittance and haze: The film of each example was attached to the ink surface of CG glass and the transmittance and haze of the test piece were measured using a haze meter. The total transmittance and haze of the pressure-sensitive adhesive film were obtained by subtracting the measured values ​​from the total transmittance and haze of the CG glass.

[0073] (5) Gel rate: Accurately weigh the film mass, recorded as m1, wrap it with a 400-mesh SUS net and completely immerse it in a mixed liquid of ethyl acetate and toluene (mass ratio 1 / 1). Take it out and dry it after three days, and weigh the film mass m2. The gel rate is calculated according to the formula (m1-m2) / m1.

[0074] (6) Step filling: Transfer the film to PET and attach it to the glass with a cross-shaped ink step. After degassing, let it stand for 1 day and observe the filling of the ink step. If there are no bubbles, it is marked as ○; if there are bubbles, it is marked as ╳.

[0075] (7) Holding force: Peel off one side of the polyester film (release film) of the film with the ratio 1-9, and stick it on a 0.05MM transparent PET film. Cut it into samples with a width of 25.4 mm and a length of 160 mm. Prepare the sample according to the method of GB / T4851-2014, hang it in a 70℃ holding force box, and record the drop situation. If the displacement at 72H is <2mm, it is recorded as +; if the displacement at 72H is >2mm or it falls, it is recorded as -.

[0076] The test results are shown in Table 2 below:

[0077] Table 2

[0078]

[0079]

[0080] As shown in the table above, the tape products obtained by the ratios 1, 2, 3, 4, and 6 all meet the application characteristics of high viscosity (peel force), low refractive index, good cohesion (retention force), and good wettability (gel rate and step filling). Due to the improper combination of curing agents, the gel rate of ratio 5 is not within the range required by the present invention, and it has poor wettability and low viscosity, which cannot meet the application requirements. The preparation conditions of the adhesive compositions corresponding to ratios 7 to 10 do not meet the scope required by the present invention. For example, comparative example 1 does not select fluorine-containing monomers, and its refractive index cannot meet the requirements; the functional monomer content used in comparative example 2 is low, and its viscosity cannot meet the requirements; comparative example 3 does not select long-chain monomers, and the obtained tape products cannot meet the application requirements in terms of viscosity, wettability, etc. In summary, for applications requiring low refractive index and high viscosity, the monomer synergy described in the present invention is indispensable.

[0081] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. An adhesive tape product, characterized in that: It is prepared by the following steps: 98-99.9 parts by weight of the low-refractive adhesive composition and 0.1-2 parts by weight of the curing agent are mixed, the mixture is evenly mixed and coated on a release film, baked at 100-120° C. for 1-4 minutes, and then another layer of release film is attached to the surface, and aged at 50-70° C. for 72 hours to obtain a tape product; The curing agent is selected from one or more of an isocyanate curing agent, an epoxy resin curing agent, an aziridine curing agent, and a metal chelate compound curing agent; When the acrylate functional monomer contains a hydroxyl group, an isocyanate curing agent is selected; when the acrylate functional monomer contains a carboxyl group, one or more of an isocyanate curing agent, an epoxy resin curing agent, an aziridine curing agent, and a metal chelate compound curing agent is selected; Wherein, the low-refractive adhesive composition comprises the following components in parts by weight: 40-85 parts of long-chain acrylate monomer, 5-15 parts of hydroxyl- or carboxyl-containing acrylate functional monomer, 10-50 parts of fluorine-containing acrylate monomer, 50-200 parts of solvent and 0.2-2 parts of initiator; The preparation method of the low-refractive adhesive composition comprises the following steps: 1) Add 40-85 parts of long-chain acrylate monomer, 5-15 parts of acrylate functional monomer, 10-50 parts of fluorinated acrylate monomer, and 50-200 parts of solvent into a reactor, pass nitrogen for 20-40 minutes under stirring conditions, maintain the temperature above 75°C, add 0.1-1 parts of initiator and react for 2-10 hours; 2) raising the temperature to above 78° C., adding 0.1-1 parts of an initiator, and reacting for 2-10 hours; cooling to obtain the low-refractive adhesive composition; The long-chain acrylic acid ester monomer is selected from isooctyl acrylate, and the fluorine-containing acrylic acid monomer is selected from tridecafluorooctyl acrylate.

2. The adhesive tape product according to claim 1, characterized in that: The acrylate functional monomer is selected from one or more of acrylic acid, methacrylic acid, hydroxyethyl acrylate, hydroxyethyl methacrylate, hydroxypropyl acrylate, and hydroxypropyl methacrylate.

3. The adhesive tape product according to claim 1, characterized in that: The initiator is one or more of an azo initiator and a peroxide initiator.

4. The adhesive tape product according to claim 3, characterized in that: The initiator is one of azobisisobutyronitrile and benzoyl peroxide or a mixture of the two.

5. The adhesive tape product according to claim 1, characterized in that: The epoxy resin curing agent is selected from: one or more of P-(2,3-epoxypropoxy)-N,N-di(2,3-epoxypropyl)aniline, triglycidyl-m-aminophenol, 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane, and N,N,N',N'-tetraepoxypropyl-4,4'-diaminodiphenylmethane; The aziridine curing agent is selected from: one or more of trimethylolpropane-tris[3-(2-methylaziridinyl) propionate], pentaerythritol tris[(3-(1-aziridinyl) propionate], and trimethylolpropane tris(3-aziridinyl propionate); The metal chelate compound curing agent is selected from one or more of: aluminum triacetylacetonate, iron triacetylacetonate, ruthenium triacetylacetonate, zinc diacetylacetonate, titanium triacetylacetonate, zirconium tetraacetylacetonate, tri(2,4-hexanedione)aluminum.

Citation Information

Patent Citations

  • Pressure-sensitive adhesive composition, pressure- sensitive adhesive sheet, and optical film

    JP2002363523A